Ab-initio investigation of electronic and magnetic properties of the 18-valence-electron fully-compensated ferrimagnetic (CrV)XZ Heusler compounds: A prototype for spin-filter materials - Ozdogan, K.; Sasioglu, E.; Galanakis, I. (ELSEVIER, 2015)
Spin-filter materials are magnetic semiconductors susceptible of improving the performance of magnetic tunnel junction based spintronic devices. Using state-of-the-art ab initio electronic structure calculations, we exploit the electronic and magnetic properties of (CrV)XZ quaternary Heusler compounds having 18 valence electrons per formula unit. All compounds under study have been found to combine fully-compensated ferrimagnetism to magnetic semiconducting behavior and some are even gapless or spin-gapless semiconductors. Our results pave the way for incorporating these compounds in spintronic and magnetoelectronic devices. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Fully-compensated ferrimagnetic Heusler compounds; Magnetic semiconductors; Spin-gapless semiconductors; BAND-STRUCTURE; 1ST-PRINCIPLES; SEMICONDUCTORS; Materials Science